Hubungan Beban Kerja, Durasi Kerja, dan Stress Kerja dengan Kelelahan Kerja Karyawan Bank X Tahun 2021: Relationship between Workload, Work Duration and Work Stress with Work Fatigue of Bank X Employees in 2021 - Kadir, Mala (MPI Press, 2023)
Introduction: Achieving the company's targets will trigger employees to work stressfully, resulting in physical and psychological fatigue due to work. Objectives: This study aims to determine the relationship between workload, duration, and work stress to work fatigue at Bank X in 2021 Method: This research uses quantitative research with a cross-sectional method. This research will focus on finding the relationship between workload, work duration, and work stress on work fatigue in Bank X employees in 2021. The population in this study is all employees at Bank Fed Up. The total number of Bank X employees in December 2021 was recorded at 32 people. The instrument used in this research was a questionnaire tested for validity and reliability first. The bivariate analysis in this study used the Chi-Square test with a significance level of 0.05. Result: After carrying out the chi-square test, the relationship between workload and work fatigue was obtained, the value obtained was 0.000. The relationship between work duration and work fatigue is 0.008. The relationship between work stress and work fatigue and the value is 0.530. Conclusion: There is a relationship between workload work duration and work fatigue among Bank X employees in 2021. There is no relationship between work stress and work fatigue in the Bank